2018
DOI: 10.1016/j.jped.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Videothoracoscopic surgery before and after chest tube drainage for children with complicated parapneumonic effusion

Abstract: Videothoracoscopic surgery is a highly effective procedure for treating children with complicated parapneumonic pleural effusion. When videothoracoscopic surgery is indicated in the presence of loculations (stage II or fibrinopurulent), no difference were observed in time of clinical improvement and hospital stay among the patients with or without chest tube drainage before videothoracoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, in the recent decades, studies published in literature showed how early surgery can guarantee a series of benefits, such as a reduction in hospital stay, fewer complications, and a faster recovery of respiratory function. Indeed, several studies in literature demonstrated the safety and efficacy of VATS in the treatment of PE in the pediatric population, observing how this approach is associated with a short recovery time, excellent aesthetic results, reduced post-operative pain and low complication rate [ 19 , 20 ].…”
Section: Video-assisted Thoracoscopymentioning
confidence: 99%
“…However, in the recent decades, studies published in literature showed how early surgery can guarantee a series of benefits, such as a reduction in hospital stay, fewer complications, and a faster recovery of respiratory function. Indeed, several studies in literature demonstrated the safety and efficacy of VATS in the treatment of PE in the pediatric population, observing how this approach is associated with a short recovery time, excellent aesthetic results, reduced post-operative pain and low complication rate [ 19 , 20 ].…”
Section: Video-assisted Thoracoscopymentioning
confidence: 99%
“…(Gupta et al, 2018) Over time a big number of drugs have been developed against drug-resistant pathogens and some drugs are still developing. Reasonable use of antibiotics, starting with narrow spectrum drugs and the shortest possible duration may help in reducing the drug resistance (Arbo et al, 2019; Osowicki & Steer, 2019).Complications such as emphysema and lung abscess often need surgery procedures in addition to antibiotic treatment such as video-assisted thoracoscopy or insertion of percutaneous small-bore drainage with instillation of fibrinolytics(Arbo et al, 2019;Gupta et al, 2018;Haji et al, 2018;Knebel et al, 2018;Shan et al, 2019). Repeated ultrasounds may be required in the monitoring these patients, in the case of clinical deterioration as fluid may accumulate rapidly(Knebel et al, 2018;Williams et al, 2016).…”
mentioning
confidence: 99%